Penyelesaian Sengketa Medis Antara Pasien Atau Keluarga Pasien Dengan Dokter Berdasarkan Ketentuan Hukum di Indonesia - Tiberius Zaluchu; Dhoni Yusra (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
Health development is very important according to the Preamble to the 1945 Constitution of the Republic of Indonesia. Health as a human right is manifested in various efforts, including through the implementation of medical practice where the role of doctors is very important. In its implementation sometimes causes problems that lead to medical disputes. The formulation of the problem in this research are: How is the arrangement of medical dispute resolution between patient/patient's family and doctor based on applicable regulations and How is the process of fair medical dispute resolution between patient/patient's family and doctor based on law number 29 of 2004 concerning medical practice. The method used in this research is normative juridical. Used to find out and get a comprehensive picture by looking at the facts related to the problem so that it can prove the problem in order to get a scientific answer. The results of this study indicate that: The existing medical dispute resolution arrangements are still scattered in various laws and regulations, resulting in overlapping medical dispute resolution arrangements which in the end have the potential to cause ambiguity and uncertainty in their resolution. And in terms of a just settlement of medical disputes between patients/patients' families and doctors based on Law Number 29 of 2004 concerning medical practice, it begins with the medical professional institution, namely the Medical Ethics Honorary Council (MKEK) or the Indonesian Medical Discipline Honorary Council (MKDKI). . If it is not completed, the settlement can be continued with non-professional institutions in the form of: Civil (non-litigation and litigation); criminally or administratively/state administration. Settlement of non-litigation or litigation can be chosen in accordance with the availability of evidence and the case position or legal facts.